Segregation of Hydroxycinnamic Acid Esters Mediating Sweetpotato Weevil Resistance in Storage Roots of Sweetpotato - Anyanga, Milton O.; Yada, Benard; Yencho, G. C.; Ssemakula, Gorrettie N.; Alajo, Agnes; Farman, Dudley I.; Mwanga, Robert O. M.; Stevenson, Philip C. (Frontiers in Plant Science, 2017)
Resistance to sweetpotato weevils, (Cylas spp.) has been identified in several sweetpotato (Ipomoea batatas) landraces from East Africa and shown to be conferred by hydroxycinnamic acids that occur on the surface of storage roots. The segregation of resistance in this crop is unknown and could be monitored using these chemical traits as markers for resistance in F1 offspring from breeding programmes. For the first time in a segregating population, we quantified the plant chemicals that confer resistance and evaluated levels of insect colonisation of the same progeny in field and laboratory studies. We used a bi-parental mapping population of 287 progenies from a cross between I. batatas ‘New Kawogo’, a weevil resistant Ugandan landrace and I. batatas ‘Beauregard’ a North American orange-fleshed and weevil susceptible cultivar. The progenies were evaluated for resistance to sweetpotato weevil, Cylas puncticollis at three field locations that varied climatically and across two seasons to determine how environment and location influenced resistance. To augment our field open-choice resistance screening, each clone was also evaluated in a no choice experiment with weevils reared in the laboratory. Chemical analysis was used to determine whether differences in resistance to weevils were associated with plant compounds previously identified as conferring resistance. We established linkage between field and laboratory resistance to Cylas spp. and sweetpotato root chemistry. The data also showed that resistance in sweetpotato was mediated by root chemicals in most but not all cases. Multi-location trials especially from Serere data provided evidence that the hydroxycinnamic acid esters are produced constitutively within the plants in different clonal genotypes and that the ecological interaction of these chemicals in sweetpotato with weevils confers resistance. Our data suggest that these chemical traits are controlled quantitatively and that ultimately a knowledge of the genetics of resistance will facilitate management of these traits, enhance our understanding of the mechanistic basis of resistance and speed the development of new sweetpotato varieties with resistance to sweetpotato weevil.